2020
DOI: 10.3390/genes11010075
|View full text |Cite|
|
Sign up to set email alerts
|

Pigment Intensity in Dogs is Associated with a Copy Number Variant Upstream of KITLG

Abstract: Dogs exhibit a wide variety of coat color types, and many genes have been identified that control pigment production, appearance, and distribution. Some breeds, such as the Nova Scotia Duck Tolling Retriever (NSDTR), exhibit variation in pheomelanin pigment intensity that is not explained by known genetic variants. A genome-wide association study comparing light red to dark red in the NSDTR identified a significantly associated region on canine chromosome 15 (CFA 15:23 Mb–38 Mb). Coverage analysis of whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 62 publications
3
53
0
Order By: Relevance
“…In mudis, this color is referred to as “grey-brown”. The mudis in (E) and (F) have two copies of the recessive e allele of the MC1R gene, that affects phaeomelanin and results in varying shades of cream [ 4 , 10 , 13 , 14 , 15 , 16 ]. Additionally, the mudi in (E) is homozygous for d 3 , thus showing grey pigmentation on the nose and eye rims, and a lightened eye color.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mudis, this color is referred to as “grey-brown”. The mudis in (E) and (F) have two copies of the recessive e allele of the MC1R gene, that affects phaeomelanin and results in varying shades of cream [ 4 , 10 , 13 , 14 , 15 , 16 ]. Additionally, the mudi in (E) is homozygous for d 3 , thus showing grey pigmentation on the nose and eye rims, and a lightened eye color.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of MLPH variants on melanosome transport and pigmentation are distinct from the recently identified variants of phaeomelanin-based pigment intensity, which also perturb the perceived depth of coloration, although resulting coat colors are varying shades of red, cream, and white [ 4 ]. Nevertheless, the previously identified d 1 and d 2 MLPH variants do not explain all of the dilute coat color phenotypes in canids, and a recent report suggests that additional coat color alleles are likely present at low frequency throughout the canine population [ 2 , 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether and regardless of other genetic reasons for melanism, e.g., [17][18][19][20][21][22][23], investigation of segregation of both alleles, mutated and non-mutated, in a set of 495 samples produced a perfect association resulting in extremely high statistical support under different scenarios and providing strong arguments that the mutation c.33.G>T causes the black phenotype in European roe deer. Considering the high frequency of melanistic individuals in the North-West German lowland population, it cannot be excluded that melanism had a selective advantage (e.g., camouflage) as previously discussed for other species [3,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, dogs that were homozygous for the mutation still showed variation in pheomelanin dilution within some breeds, suggesting that pheomelanin dilution is a multigenic trait both across and within breeds. Similarly, a third study identified a copy number variant upstream of the KIT ligand gene ( KITLG ) that was predictive of red intensity in Nova Scotia Duck Tolling Retriever and Poodle [ 32 ], but not in two of the most common (in the United States [ 33 ]) and phenotypically variable breeds: Golden Retriever and Labrador Retriever. In this study, our aim was to increase understanding of the genetic underpinnings of coat pheomelanin intensity variation in dogs by testing whether there are additional loci that affect intensity across dog breeds, and investigating how these loci might interact.…”
Section: Introductionmentioning
confidence: 99%